2016
DOI: 10.1002/lt.24428
|View full text |Cite
|
Sign up to set email alerts
|

The evolving threat of carbapenem‐resistant infections after liver transplantation: The case of A cinetobacter baumannii

Abstract: Postoperative bacterial infections have shifted from predominantly gram-positive to gram-negative organisms in liver transplantation (LT) recipients.(1) Of concern is the increasing incidence of difficult to treat multidrug resistant (MDR) infections due to extended spectrum b-lactamases and carbapenemresistant Enterobacteriacae. The high mortality rate (40%-70%) associated with post-LT carbapenemresistant Klebsiella pneumoniae (CRKP) infections is a sobering example of the impact of MDR infection in this popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
6
1
Order By: Relevance
“…We screened 998 stool samples and 119 rectal swabs (median, 8 [IQR, [4][5][6][7][8][9][10][11][12] samples per patient). Rectal swabs were taken predominantly in the early posttransplant period and were associated with less MDRO recovery than stool specimens ( In the cohort, 23 of 97 (23%) bacterial infection episodes were due to MDRO (Supplementary Table 1).…”
Section: Mdro Colonization and Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…We screened 998 stool samples and 119 rectal swabs (median, 8 [IQR, [4][5][6][7][8][9][10][11][12] samples per patient). Rectal swabs were taken predominantly in the early posttransplant period and were associated with less MDRO recovery than stool specimens ( In the cohort, 23 of 97 (23%) bacterial infection episodes were due to MDRO (Supplementary Table 1).…”
Section: Mdro Colonization and Infectionmentioning
confidence: 99%
“…Multidrug-resistant organisms (MDROs) represent an important cause of morbidity and mortality after solid organ transplantation (SOT) [1][2][3]. SOT recipients colonized with MDROs may serve as important reservoirs of MDRO transmission across the healthcare setting [4]. Elucidating mechanisms of MDRO colonization, infection, and transmission in SOT recipients is thus an urgent priority.…”
mentioning
confidence: 99%
“…We and others have demonstrated a critical role for intestinal MDRB colonization prior to the development of infection 4,5 . MDRB infections, in turn, significantly impact post-LT survival 46 , making colonization by MDRB a critical factor in the transplant-related clinical course. Recipients of LT receive frequent and sustained antibiotic regimens and routinely experience adverse clinical events after transplantation 4,7 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the 30-day mortality rate calculated in our study was higher than the previously reported 60-day mortality rate (46.4%) for LT recipients with CRAB infections. 21 Furthermore, in our study, the initial mortality rate was high after CRAB-B detection, with a cumulative incidence of 58.6% at 5 days, which can be attributed to the high fatality of CRAB-B among CRAB infections after LT. Therefore, timely optimal treatment for CRAB-B, such as proper antibacterial and immunosuppression modification, is necessary.…”
Section: Discussionmentioning
confidence: 47%